Analysis and Proposed Service Quality Improvement of PT. Prudential Life Insurance Indonesia - Iqbal, Mohammad; Yudoko, Gatot (Journal of Business and Management, 2014)
Abstract. This study aimed to determine the level of satisfaction of the policy holders in PT . Prudential Life Insurance Indonesia over the quality of service provided to the policy holder until today . In this study , the writer used SERVQUAL as a measure of a company's services to the consumerâ€™sÂ  satisfaction . This study used a questionnaire which was distributed to 170 respondents as a consumer of product in PT . Prudential . Questionnaire results shows that the level of customer satisfaction dimensions of service quality assurance , reliability , empathy , responsiveness and tangible need a lot of improvement . Analysis results prove that there is a gap between perception and expectation. Of the analysis indicated that there are no services that need to be fixed with high interest. PT Prudential just need to maintain existing services ( i.e. in the dimension of assurance , empathy , responsiveness and reliability) and not too much in making attempts on dimensions of service that do not really matter ( in this case is the dimension of tangibles )Keywords: PT. Prudential Indonesia, service, quality, service quality, SERVQUAL, gap, improvements